2021
DOI: 10.1038/s41598-021-88291-8
|View full text |Cite
|
Sign up to set email alerts
|

Subunit vaccine protects against a clinical isolate of Mycobacterium avium in wild type and immunocompromised mouse models

Abstract: The nontuberculous mycobacteria (NTM) Mycobacterium avium is a clinically significant pathogen that can cause a wide range of maladies, including tuberculosis-like pulmonary disease. An immunocompromised host status, either genetically or acutely acquired, presents a large risk for progressive NTM infections. Due to this quietly emerging health threat, we evaluated the ability of a recombinant fusion protein ID91 combined with GLA-SE [glucopyranosyl lipid adjuvant, a toll like receptor 4 agonist formulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…However, it should be noted that the degree of lung inflammation is not plainly associated with the efficacy of immunization. Our observations are consistent with previous reports [ 25 , 34 , 75 ] in which lung pathology scores did not correlate with the bacterial loads in the context of Mav infection, suggesting that protective immune responses minimally require some immune cell components and antigen-specific but vigorous immune responses.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it should be noted that the degree of lung inflammation is not plainly associated with the efficacy of immunization. Our observations are consistent with previous reports [ 25 , 34 , 75 ] in which lung pathology scores did not correlate with the bacterial loads in the context of Mav infection, suggesting that protective immune responses minimally require some immune cell components and antigen-specific but vigorous immune responses.…”
Section: Discussionsupporting
confidence: 93%
“…Although the protective immune correlates of the host against MAC infection have not been fully elucidated to date, two studies recently documented that ID91 and Ag85B antigen-specific multiple cytokine-expressing CD4 + T cells [ 25 ] or the reciprocal induction of both antigen-specific Th1 and Th17 cells are important for the control of Mav infection [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analyses were performed using GraphPad Prism 7 software. Significant differences are labeled accordingly in the figures where * p < 0.05, ** p < 0.01, *** p < 0.001 and **** p < 0.0001, with methodology used previously by our group 68,70 .…”
Section: Methodsmentioning
confidence: 99%
“…In an experiment involving immunocompromised beige mice that were deficient in B and T lymphocytes, natural killer cells, and had reduced bactericidal activity, administration of the BCG vaccine showed reduced pulmonary bacterial burden in the lungs and spleen of these mice compared to C57BL/6 mice when both were challenged with M. avium. As a result, this study demonstrated that prophylactic immunization with the BCG vaccine tended to lower immunopathology within beige mice infected with M. avium [ 78 ]. Furthermore, the use of DNA plasmids and recombinant forms of the BCG vaccine encoding single mycobacterial genes has been shown to provide great protective effects against M. avium infection.…”
Section: Mycobacterium Aviummentioning
confidence: 99%